(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article explores the role of reading in learning English and emphasizes its importance in developing language proficiency. Reading, as one of the core language skills, plays a crucial role in enriching vocabulary, reinforcing grammar, and improving both pronunciation and writing. The study discusses the benefits of intensive and extensive reading, strategies for fostering independent reading habits, and the motivational impact of reading activities. The paper concludes that integrating regular reading practice significantly enhances learners’ overall English language competence and interest in language learning.